[Capsis, Paul (singer) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Paul Capsis (born 1964) is an Australian singer and actor whose extensive career has included theatre, live concerts, cabaret, film, and television. Capsis has worked with many leading Australian theatre companies such as the Sydney Theatre Company, Melbourne Theatre Company, Malthouse Theatre and Company B Belvoir, and further programs featuring him are located within these seperate PROMPT files. He has won multiple Helpmann and Green Room Awards, as well as others, for his work on stage, in cabaret and in film. [Information from the Creative Representation creativerep.com.au website, 2018.]
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Capsis, Paul, -- 1964- -- Miscellanea; Actors -- Australia -- Miscellanea; Singers -- Australia -- Miscellanea; Entertainers -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian